PENGARUH MEDIA MUSIK INSTRUMENTAL TERHADAP KETERAMPILAN MEMBACA PUISI KELAS V SDS Al-MADANI PONTIANAK - Priadi, Aam; Marzuki, Marzuki; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem of this research is how the instrumental music media on the poetry reading skills of class V SDS Al-Madani Pontianak. The purpose of this study was to analyze the influence of instrumental music media on the poetry skill of class V SDS Al-Madani Pontianak. The method used is experimental method with pre-experimental design with one group prestest-posttest design. The population of all students of class V of SDS Al-Madani, andÂ 41 samples consisting of 20 men and 21 women with nonprobability sampling technique sampling with saturated sampling type. Technique Data collection used in this research that is using measurement technique. The data collection tool used is the poetry reading test. Based on the result of data analysis in the executive class, the pretest value is 59,348 and the posttest average is 81,299. The result of test of hypothesis data (t-test) dependent obtained t 11,827)> t (2,021), significant level (Î± = 5% and dk = 41 - 1 = 40) equal to 2,021, hence Ha accepted, instrumental music to the poetry reading skills of class V Elementary School of Private Al-Madani Pontianak. Calculation of Effect Size obtained ES = 0.1557 (low criteria). This means that the instrumental music media has an effect on the poetry skill of class V SDS Al-Madani Pontianak. Keywords: Influence, Instrumental Music Media, Reading Poetry